Mobile network quality of experience using big data analytics approach - Yusuf-Asaju, Ayisat W.; Md Dahalin, Zulkhairi; Ta'a, Azman (2017)
Traditionally, Quality of experience is mostly examined in a laboratory experiments to enable a fixed contextual factor. While the results present an estimated mean opinion score representing perceived QoE.It is imperative to estimate mean opinion score employing large data (big data) gathered from the mobile network comprising of different user's location and time for a specific service. Because time and location can have a huge influence on the user perceived quality of experience.Therefore, this paper proposed a framework for modelling perceived QoE through big data analytics.The proposed framework describes the process of estimating perceived quality of experience to assist the mobile network operators effectively manage the network performance and aid satisfactory provision of mobile internet services.